EFEKTIVITAS VULVA HYGIENE MENGGUNAKAN EKSTRAK DAUN SIRIH TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI PMB IT - Redjeki, Sri (Journal of Midwifery Tiara Bunda, 2022)
The infection that often occurs in mothers after giving birth is infection of the perineum. From some of the literature and journals above, it can be seen that respondents who used betel leaf after 5 days post partum, (62.5%) had dry perineal wounds while respondents who did not use betel leaf (37.5%) experienced perineal wound healing on the following day. 8th. This study aims to explain the effectiveness of betel boiled water in healing second degree perineal wounds. The method in this study is a Literature Review with a Quasi-experimental research design with a posttest design with a control group. There are 10 journal criteria in the literature review with an assessment checklist with several questions to assess the quality of the study based on the PICOS analysis (population, intervention, outcome, study design and publication, year of publication and language). The results of analysis in 9 research journals conducted by literature reviews, almost half of which were 66.6% published in 2015, 2019, and 2020 with a small portion using cross-sectional research designs, and experimental with factorial designs. This literature review study almost partially (33.4%) used accidental sampling techniques, almost all (100%) used the observation sheet, and some 33.4% used the Mann-Whitney Test analysis. The importance of socializing betel leaf stew to postpartum mothers as an alternative to natural perineal wound care. Use boiled water of betel leaf, which is 100gr of fresh betel leaves added 1L of boiled water for 20 minutes after boiling, to get maximum results in healing perineal wounds.